2015
DOI: 10.1016/j.bbadis.2015.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin gene is predominantly regulated by histone modifications in human colon cancer and ectopic expression of the nuclear isoform induces cell death

Abstract: Clusterin (CLU) is an important glycoprotein involved in various cellular functions. Different reports have mentioned that the two isoforms of CLU; secretary (sCLU) and nuclear (nCLU) have opposite (paradoxical) roles in cancer development. sCLU provides pro-survival signal, whereas nCLU is involved in pro-apoptotic signaling. However, the molecular mechanism of CLU gene regulation is not clear as of yet. We hypothesize that CLU gene is regulated by DNA methylation and histone modifications and clusterin plays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…This effect is independent of AD diagnosis indicating that the epigenetic changes in CLU are a sign of “natural aging” contributing to disease aetiology. In the human two distinct CLU isoforms have recently been described with opposing functions in cell survival and apoptosis [ 21 , 28 , 73 , 130 , 131 ]. Our data indicate that an alternative promoter becomes epigenetically “activated” in aged neurons and the expression of a pro-apoptotic CLU isoform may contribute to degeneration predominantly in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is independent of AD diagnosis indicating that the epigenetic changes in CLU are a sign of “natural aging” contributing to disease aetiology. In the human two distinct CLU isoforms have recently been described with opposing functions in cell survival and apoptosis [ 21 , 28 , 73 , 130 , 131 ]. Our data indicate that an alternative promoter becomes epigenetically “activated” in aged neurons and the expression of a pro-apoptotic CLU isoform may contribute to degeneration predominantly in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…While, on the other hand, the molecular mechanism of action for CLUS is although unclear as of yet, but evidence suggests DNA methylation and histone modification events predominantly regulate CLUS gene (Deb et al, 2015). Moreover, mammalian development is encountered with two windows for genome-wide DNA demethylation and remethylation ie one during gametogenesis and the other post-fertilisation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mammalian development is encountered with two windows for genome-wide DNA demethylation and remethylation ie one during gametogenesis and the other post-fertilisation. While, on the other hand, the molecular mechanism of action for CLUS is although unclear as of yet, but evidence suggests DNA methylation and histone modification events predominantly regulate CLUS gene (Deb et al, 2015). Several studies have demonstrated that during intrauterine development alterations in imprinting pattern of H19, IGF2 and IGF2R to be associated with placental and foetal developmental abnormalities (Buckberry, Bianco-Miotto, Hiendleder, & Roberts, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Besides TETs-mediated DNA demethylation, ascorbate could also regulate histone demethylation by serving as a cofactor for the JmjC domain-containing histone demethylases, which, like TETs, also belong to the iron and 2-oxoglutarate -dependent dioxygenase family 3638 . Both DNA demethylation and histone demethylation are involved in regulating CLU transcription 39, 40 , and potentially alternative splicing, which could be instrumental to explain the differential effect of ascorbate on secreted CLU and nuclear CLU. Thus, elucidating the detailed epigenetic, or other, mechanism of ascorbate in suppressing CLU expression, especially the secreted CLU isoform, is ensured in future studies.…”
Section: Discussionmentioning
confidence: 99%